ARE THEY WATCHING? TEST-TAKER VIEWING BEHAVIOR DURING AN L2 VIDEO LISTENING TEST - Elvis Wagner (Language Learning and Technology)
The accessibility of video technology has made it possible to utilize both the auditory and visual channels to present listening texts in the second language (L2) classroom and on L2 listening tests. However, there has been little research investigating the extent to which L2 listeners actually watch the video monitor when presented with a listening video text. The current study investigated test-taker behavior on an L2 video listening test. Thirty-six test-takers were videotaped while taking a listening test composed of six separate video texts, and the amount of time test-takers made eye contact with the video monitor was computed. An analysis of the data indicated that the group of participants oriented to the video monitor 69% of the time while the video text was played. In addition, the study yielded valuable information concerning the consistency of the test-takers’ viewing behavior.